2008
DOI: 10.1017/s0266467408004951
|View full text |Cite
|
Sign up to set email alerts
|

The utilization of large savanna trees by elephant in southern Kruger National Park

Abstract: Abstract:Elephant are believed to be one of the main ecological drivers in the conversion of savanna woodlands to grassland. We assessed the impacts of elephant on large trees (≥5 m in height) in the southern section of the Kruger National Park. Tree dimensions and utilization by elephant were recorded for 3082 individual trees across 22 transects (average length of 3 km and 10 m wide). Sixty per cent of the trees exhibited elephant utilization and 4% were dead as a direct result of elephant foraging behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
138
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 34 publications
(62 reference statements)
1
138
1
Order By: Relevance
“…The relatively lower stem density and survival rate after elephant utilization probably lead to more open woodlands in the granite lowveld. The negative correlation between elephant numbers and tree densities in most height classes in our study area, and in other areas (Cumming et al 1997;Whyte et al 2003;Shannon et al 2008;Woolley et al 2011), together with the population changes of the browser and grazer species, indicate in this instance that elephant might compete with other browsing species and facilitate grazers, especially megagrazer species, i.e., hippo, white rhino, and buffalo, through a decrease in tree cover and an increase in grass. Also, the proportion of browse consumed by other herbivores, aside from elephant, decreased over time.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The relatively lower stem density and survival rate after elephant utilization probably lead to more open woodlands in the granite lowveld. The negative correlation between elephant numbers and tree densities in most height classes in our study area, and in other areas (Cumming et al 1997;Whyte et al 2003;Shannon et al 2008;Woolley et al 2011), together with the population changes of the browser and grazer species, indicate in this instance that elephant might compete with other browsing species and facilitate grazers, especially megagrazer species, i.e., hippo, white rhino, and buffalo, through a decrease in tree cover and an increase in grass. Also, the proportion of browse consumed by other herbivores, aside from elephant, decreased over time.…”
Section: Discussionsupporting
confidence: 56%
“…Both negative and positive effects of elephants on other herbivore species have been claimed, as a consequence of the impact of elephants on the vegetation structure, biomass, and species composition. Elephants are known to push over, debark, and break trees, and various studies have found a decline in tree densities in the presence of elephants (Cumming et al 1997;Shannon et al 2008;Woolley et al 2011). Even at comparatively low elephant densities (<0.2 elephants/km 2 ), the densities of certain tree species show signs of decline (Cumming et al 1997;Shannon et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large trees play an important role within the ecosystem by providing habitat and shade to several species and food for many browsers (Shannon et al 2008), as well as increasing the nutritional status of the herbaceous layer for grazers (Treydte et al 2008). Trollope et al (1998) showed that the interaction of elephant impact and fire can have a profound effect on woody vegetation structure and composition, and suggested that an increase in elephant density (.0.36 individuals/km 2 ) could lead to structural changes across the KNP landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Kokwaro, also known as Marula is highly selected by the African elephant (Loxodonta africana Blumenbach) (Shannon et al, 2008), and hence heavily utilized (Jacobs and Biggs, 2001). The repeated browsing by elephants causes serious damage through breaking and removing of branches, and by preventing or reducing recruitment and regeneration (Balfour et al, 2007).…”
Section: Introductionmentioning
confidence: 99%